PERBANDINGAN RETURN SAHAM, VOLUME PERDAGANGAN SAHAM DAN KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER DAN AKUISISI PADA PERUSAHAAN PUBLIK YANG TERDAFTAR DI BEI - B11111049, Durisliani (Jurnal Manajemen Update, 2015)
This research aims to analyze the difference on stock returns, trading volume andfirm performance before and after mergers and acquisitions on bidding firms.Corporate performance is measured by using financial ratio: Current Ratio, Debtto Total Assets Ratio, Debt To Equity Ratio, Total Asset Turn Over, Return onAssets, Return on Equity, and Earning Per Share. Quantitative method is used inthis research, take the data of non-industrial public company finance which hadconducted mergers and acquisitions and announce its activity in the period 20062008,statisticparametricisusedtoanalyzedata.PairedSampleTTestisusedtoanswerhypothesis.The sampling method using purposive sampling and obtaineda sample of 15 companies.The results from this research show that parcial study in 9 variabel, stock returns,trading volume, Current Ratio, Debt to Total Assets Ratio, Debt To EquityRatio,Total Asset Turn Over, Return on Assets, Return on Equity, and Earning PerShare that not show the significant difference before and after mergers andacquisitions in 5 years before and after merger and acquisitions.Keywords: Mergers and acquisitions, stock returns, trading volume, financialperformace.